Family-Centered Care Coordination in an Interdisciplinary Neurodevelopmental Evaluation Clinic: Outcomes From Care Coordinator and Caregiver Reports - McNally Keehn, Rebecca; Enneking, Brett; Ramaker, Margo; Goings, Michael; Yang, Ziyi; Carroll, Aaron; Ciccarelli, Mary (Frontiers in Pediatrics, 2020)
Children with neurodevelopmental disabilities experience many unmet healthcare needs. Care coordination is one critical solution to addressing the substantial strain on families, local communities, and the larger health care system. The purpose of this study was to implement a care coordination program in an interdisciplinary pediatric neurodevelopmental evaluation clinic and examine care coordinator and caregiver outcomes. Following neurodevelopmental diagnosis, children were provided either care coordination (CC) or care as usual (CAU). For those receiving CC, the care coordinator documented family goals and care coordination activities, outcomes, and time spent. Caregivers in both groups completed a survey measuring access to needed services and caregiver stress and empowerment following their child’s evaluation (T1) and 4-6 months post-evaluation (T2). Care coordinator findings demonstrated that over 85% of family goals focused on understanding the child’s diagnosis, getting needed interventions and educational support, and accessing healthcare financing programs. More than half of care coordination activities were spent on engaging and educating the family; similarly, the most time-consuming care coordination efforts were in helping families understand their child’s diagnosis and meeting family’s basic needs. For those children referred to needed services, 54% were enrolled in one or more service at T2. Caregivers in both the CC and CAU groups reported an increase in stress related to interactions with their child as well as increased empowerment from T1 to T2. Contrary to our hypotheses, there were no significant group by time interactions across caregiver-report measures. While these findings further our understanding of care coordination delivery, they diverge from previous evidence demonstrating care coordination efficacy. This study paves the way for future opportunities to evaluate what kinds of care coordination supports families need at varying times in their child’s healthcare journey and how the outcomes important to all stakeholders are measured to reflect true evaluation of efficacy.